Step into the metaverse : how the immersive internet will unlock a trillion-dollar social economy - Van Rijmenam, Mark (Hoboken, New Jersey : John Wiley & Sons, Inc., 2022)
'In Step into the Metaverse: How the Immersive Internet Will Unlock a Trillion-Dollar Social Economy, future tech strategist, entrepreneur, and thought leader Dr. Mark van Rijmenam delivers a startlingly insightful discussion about how the world as we know it will fundamentally change as the physical and the digital worlds merge into the metaverse, impacting the everyday experiences of people, companies, and societies. The author maps out the extraordinary opportunities and challenges facing business leaders, consumers, regulators, policymakers, and other metaverse stakeholders trying to navigate the future of the Internet. In the metaverse, you can be who you want to be, where you want to be, and companies and consumers are only restricted by their own creativity how they can benefit from the immersive internet'--
The future is immersive -- Creating an open metaverse -- Be who you want to be -- Be where you want to be -- Unbound creativity for brands -- Exponential enterprise connectivity -- The creator economy -- Digitalism in the metaverse -- The future of the metaverse
Includes bibliographical references and index
Keywords: Internet -- Social aspects; Virtual reality; Human-computer interaction; Computers and civilization